Logistics Aspects Of Transport Modalities On The Exports Of Raw Sugar - Rodrigo Duarte Soliani; Pedro Paulo de Souza Guedes (European Scientific Journal, ESJ, 2016)
This work aims to present the current scenario of the Brazilian raw sugar export logistics, focusing on transportation, pointing out the benefits of intermodal road-rail in the flow of bulk sugar from mills to the Port of Santos. The study analyzes the evolution of modes of transportation and new investments focused on port infrastructure. It is possible to notice throughout the work that most of the investments in the area comes from private business groups seeking partnerships to improve competitiveness for the sector, such as Rumo Logística and America Latina Logística, which holds the largest concession and rail network in the state. The state of São Paulo currently offers transshipment options warehouses located in its territory and can meet the demand of the sugar mills to flow their product. It could be identified that the existence of a logistical planning well done using these two modes (road and rail) can guarantee competitive prices, load security and a transit time that does not compromise the receipt of the goods at the port, which historically suffer from the accumulation of vehicles, and is a great alternative for reducing air pollutants, with the reduction of vehicles circulating on the roads.